Closed Loop Analysis of Bridgeless SEPIC Converter for Drive Application - Gopinath Mani; G. Gopu (Institute of Advanced Engineering and Science, 2015)
In this paper closed loop analysis of Single phase AC-DC Bridgeless Single Ended Primary Inductance Converter (SEPIC) for Power Factor Correction (PFC) rectifier is analyzed. In this topology the absence of an input diode bridge and the due to presence of two semiconductor switches in the current flowing path during each switching cycle which will results in lesser conduction losses and improved thermal management compared to the conventional converters. In this paper the operational principles, Frequency analysis, and design equations of the proposed converter are described in detail. Performance of the proposed SEPIC PFC rectifier are carried out using Matlab Simulink software and results are presented.